2009
DOI: 10.1002/lary.20649
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric cholesteatoma and variants in the gene encoding connexin 26

Abstract: Objectives/Hypothesis: Connexin 26 is a gap junction protein encoded by the GJB2 gene. It is expressed in cholesteatoma, and mutations cause proliferative skin disorders and sensorineural hearing loss (SNHL). Deletions of GJB6, which encodes connexin 30, cause SNHL in a digenic manner with a heterozygous GJB2 mutation. We hypothesize that GJB2 and GJB6 mutations might influence the development of cholesteatoma.Study Design: Prospective observational study to identify GJB mutations in pediatric cholesteatoma.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…After genetic testing, our second patient was positive for known disease causing mutations in SLC26A and was also heterozygous for polymorphisms in GJB2 of unknown clinical significance mutation. The presence of these genetic abnormalities may suggest the possibility of genetic contributions to the formation of congenital cholesteatoma (James et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…After genetic testing, our second patient was positive for known disease causing mutations in SLC26A and was also heterozygous for polymorphisms in GJB2 of unknown clinical significance mutation. The presence of these genetic abnormalities may suggest the possibility of genetic contributions to the formation of congenital cholesteatoma (James et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous reports and suggests that miR-21 downregulates PTEN and PDCD4, leading to the proliferation of keratinocytes, 29,30,32 which is also consistent with the clinical observation of higher keratinocyte proliferation in paediatric versus adult cholesteatoma. 1,9 It has been shown that let-7 miRNA is downregulated in many solid organ tumours 33,34 and that it acts as a tumour suppressor by targeting oncogenes, including RAS and HMGA2. 35 High levels of let-7 miRNA have an antiproliferative effect on cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Connexin 26, also known as gap junction beta‐2 (GJB2), is a transmembrane protein encoded by the GJB2 gene, which is expressed in the cochlea and the skin. Mutations in the GJB2 gene have been shown to cause congenital nonsyndromic sensorineural hearing loss and hyperkeratotic skin disorders . Microarray analysis by Klenke et al revealed that the expression of GJB2 gene is higher in cholesteatoma tissue than in the skin of the external auditory canal .…”
Section: Insufficient Evidence For Genomic Instability In Cholesteatomamentioning
confidence: 99%